KAJIAN KONDISI EKSISTING FASILITAS JALUR PEDESTRIAN (STUDI KASUS JALAN SRI RATU SAFIATUDDIN BANDA ACEH) - Ruhdi Faisal; Lulusi Lulusi; Teuku Riwanda Fitri (Prodi Magister Teknik Sipil Unsyiah, 2021)
Sri Ratu Safiatuddin Street is one of the central areas of trade and culinary tourism in the city of Banda Aceh. The activities on this road vary, causing overcrowding and disruption to the performance of public facilities, including the pedestrian paths. The dysfunctional and dilapidated pedestrian path facilities cause pedestrians unable to fully utilize these facilities. Ideally, the existence of good and acceptable pedestrian path facilities can protect pedestrians from danger when concurrently using the street with other modes of transportation. Based on the above problems, this study aims to examine the conditions of the existing pedestrian path facilities on Sri Ratu Safiatuddin Street in order to meet the standards set by the Ministry of PUPR in the Guidelines for Technical Planning of Pedestrian Facilities Number 02/ SE/M/2018, divided into three aspects, namely safety, health, and environment. The data analysis method used is a quantitative method with quantitative descriptive analysis tools, which is to compare the standard criteria of technical planning guidelines for pedestrian facilities with the real conditions. The peak time for volume of pedestrians the highest was 105 pedestrians/15 minutes, the highest volume of pedestrians was 66 pedestrians/hour and the highest volume of two-way traffic was 1787 vehicles/hour. For the value of PV² = 1,5 x 108, P = 61,25 (pedestrians/hour), V = 1607 (vehicles/hour) and an average speed of 40 km/hour, a crossing recommendation is obtained in the form of a zebra crossing. The results obtained were the condition of the existing pedestrian lane facilities on Jalan Sri Ratu Safiatuddin, which showed a value of 44,02% of the facilities that had met the standard.